Approaches to the Rational Design of Molecularly Imprinted Polymers Developed for the Selective Extraction or Detection of Antibiotics in Environmental and Food Samples. Issue 13 (5th May 2021) - Jamieson, Oliver; Mecozzi, Francesco; Crapnell, Robert D.; Battell, William; Hudson, Alexander; Novakovic, Katarina; Sachdeva, Ashwin; Canfarotta, Francesco; Herdes, Carmelo; Banks, Craig E.; Snyder, Helena; Peeters, Marloes
Abstract : The World Health Organisation (WHO) reported antimicrobial resistance (AMR) as a global threat comparable to terrorism and climate change. The use of antibiotics in veterinary or clinical practice exerts a selective pressure, which accelerates the emergence of antimicrobial resistance. Therefore, there is a clear need to detect antibiotic residues in complex matrices, such as water, food, and environmental samples, in a fast, selective, cost‐effective, and quantitative manner. Once problematic areas are identified, can extraction of the antibiotics then be carried out to reduce AMR development. Molecularly imprinted polymer (MIPs) are synthetic recognition elements produced through the biomarker of interest being used as a template in order to manufacture tailor‐made ligand selective polymeric recognition sites. They are emerging steadily as a viable alternative to antibiotics, especially given their low‐cost, superior thermal and chemical stability that facilitates on‐site detection, simplified manufacturing process, and avoiding the use of animals in the production process. In this paper, the authors critically review literature from primarily 2010–2020 on rational design approaches used to develop MIPs for sensing and extraction of antibiotics, providing an outlook on crucial issues that need to be tackled to bring MIPs for antibiotic sensing to the market. Abstract : Antimicrobial resistance occurs when the organisms that cause infection evolve to survive treatments. While resistance is a natural biological phenomenon, this is accelerated by the misuse of antibiotics. The ToC image reflects different ways of how antibiotics find their way in the environment. The use of polymer‐based sensors that identify high (local) concentrations of antibiotics is discussed.